Reconstruction of Islamic Educational Leadership: Integrating Moral Responsibility and Structural Authority in the Perspective of the Qur’an and Hadith - Zulfa Rahmat Hidayati; Ahmad Syukri Saleh; Ahmad Husein Ritonga (Studi Multidisipliner: Jurnal Kajian Keislaman, 2026)
This study examines the concept of Islamic education leadership in the perspective of the Qur'an and Hadith. This research is motivated by the imbalance between managerial ability and moral integrity of leaders in a number of modern Islamic educational institutions, as well as the tendency of previous studies that are more normative and have not provided an applicative framework to contemporary leadership challenges. This research aims to analyze the concept of Islamic educational leadership, identify the relationship between the dimensions of authority and responsibility, and reconstruct Islamic education leadership models that are relevant to the needs of today's educational institutions. This research uses a qualitative approach with the type of library research. The main sources of research include classical texts such as Al-Mawardi's Al-Ahkām as-Sulthāniyyah and Al-Ghazali's Iḥyā' 'Ulūm ad-Dīn, as well as the thought of modern figures such as Ibn Taymiyyah, Muhammad Abduh, and Fazlur Rahman. Data was analyzed using descriptive-analytical techniques through the stages of data reduction, data presentation, and conclusion drawing with the theoretical framework of Islamic transformative leadership. The results of the study show that the ideal leadership of Islamic education requires a balance between al-quwwah (managerial capacity and professionalism) and al-amānah (moral integrity and spiritual responsibility), as reflected in Q.S. Al-Qashash verse 26 and Q.S. Al-Baqarah verse 30. The study also found that the synthesis between classical and contemporary thought resulted in a transformative Islamic leadership model that was able to address the challenges of professionalism, institutional governance, and social change in modern Islamic education. This study makes a new contribution in the form of the formulation of an Islamic educational leadership model that integrates the spiritual and managerial dimensions applicatively.